The effect of substance P and its common in vivo‐formed metabolites on MRGPRX2 and human mast cell activation - Lin Hsin; Nithya A. Fernandopulle; Jie Ding; Chris Lumb; Nicholas Veldhuis; John A. Karas; Susan E. Northfield; Graham A. Mackay (Wiley, 2022)
Abstract The tachykinin neuropeptide substance P (SP) is the canonical agonist peptide for the neurokinin 1 receptor (NK1R). More recently, it has also been shown to activate the Mas‐related G protein‐coupled receptor X2 (MRGPRX2) receptor on mast cells (MCs), triggering degranulation and release of inflammatory mediators. SP undergoes rapid C‐terminal truncation in vivo by a number of proteases to generate the metabolites SP(1-9)‐COOH and in particular SP(1-7)‐COOH. While the C terminus of SP is critical for NK1R activation, studies have shown that the peptide polycationic N terminus is key for MRGPRX2 and mast cell activation. The study thus aimed to determine if the C‐terminally truncated metabolites of SP, SP(1-9)‐COOH, and SP(1-7)‐COOH retained stimulatory activity at MRGPRX2. SP, SP(1-9)‐COOH, and SP(1-7)‐COOH were synthesized and tested on HEK293 cells expressing NK1R or MRGPRX2, and LAD2 human mast cells, to determine the activity of SP and its metabolites in Ca2+ mobilization, degranulation, and cytokine assays. As expected from prior studies, both C‐terminally truncated SP metabolites had essentially no activity at NK1R, even at very high concentrations. In contrast, the in vivo metabolite of SP, SP(1-9)‐COOH retained ability to activate MRGPRX2 across all parameters tested, albeit with reduced potency compared to intact SP. SP(1-7)‐COOH did not produce any significant MRGRPX2 activation. Our results suggest that the SP metabolite, SP(1-9)‐COOH, may play a regulatory role through the activation of MRGPRX2. However, given the relatively low potency of both SP and SP(1-9)‐COOH at MRGPRX2, additional work is needed to better understand the biological importance of this expanded SP/MRGPRX2 pathway.